Phases of string stars in the presence of a spatial circle - Jinwei Chu (Journal of High Energy Physics)
Abstract In string theory, black holes are expected to transition into string stars as their Hawking temperatures approach the Hagedorn temperature. We study string stars and their phase transitions in the Euclidean spacetime ℝ d × S τ 1 $$ {\mathbbm{S}}_{τ}^1 $$ × S z 1 $$ {\mathbbm{S}}_z^1 $$ . Using the Horowitz-Polchinski (HP) effective field theory, we discover novel solutions for d = 2. The uniform string star exhibits a scaling symmetry that results in the absence of a critical point for its transition into the non-uniform solution. For d = 4, we show that quartic corrections to the effective action resolve the mass degeneracy of uniform string stars. At d = 5, we find that as non-uniformity increases, the quartic terms become significant (while higher-order terms remain negligible) and reverse the direction of temperature variation, leading to a swallowtail-type phase diagram in the canonical ensemble. Extending the quartic-corrected EFT to d = 6, we find that string stars with small non-uniformity dominate the microcanonical ensemble but not the canonical ensemble, similar to the d = 5 case. However, in the microcanonical ensemble, the uniform string star is anomalously (un)stable when the spatial circle is larger (smaller) than the critical size.